Synthesis and bioevaluation of new tacrine-cinnamic acid hybrids as cholinesterase inhibitors against Alzheimer's disease. (1st January 2018) - Chen, Yao; Zhu, Jie; Mo, Jun; Yang, Hongyu; Jiang, Xueyang; Lin, Hongzhi; Gu, Kai; Pei, Yuqiong; Wu, Liang; Tan, Renxiang; Hou, Jing; Chen, Jingyi; et al.
Abstract: Small molecule cholinesterases inhibitor (ChEI) provides an effective therapeutic strategy to treat Alzheimer's disease (AD). Currently, the discovery of new ChEI with multi-target effect is still of great importance. Herein, we report the synthesis, structure–activity relationship study and biological evaluation of a series of tacrine-cinnamic acid hybrids as new ChEIs. All target compounds are evaluated for their in vitro cholinesterase inhibitory activities. The representatives which show potent activity on cholinesterase, are evaluated for the amyloid β-protein self-aggregation inhibition and in vivo assays. The optimal compound19, 27, and30 (human AChE IC50  = 10.2 ± 1.2, 16.5 ± 1.7, and 15.3 ± 1.8 nM, respectively) show good performance in ameliorating the scopolamine-induced cognition impairment and preliminary safety in hepatotoxicity evaluation. These compounds deserve further evaluation for the development of new therapeutic agents against AD.